Strategi Komunikasi Pemasaran dalam Promosi Digital Bakpia Kukus Tugu Jogja Melalui Media Sosial untuk Membangun Kesadaran Merek Dengan Model SOSTAC - Sulistyo Hadi (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
This study aims to analyze the digital marketing communication strategy of Bakpia Kukus Tugu Jogja in building brand awareness through the TikTok platform using the SOSTAC model (Situation, Objectives, Strategy, Tactics, Action, Control). The background of this research is based on the high competition in the souvenir industry in Yogyakarta and the importance of optimizing social media as a digital marketing tool. This study employs a qualitative approach using observation methods, in-depth interviews, and documentation. The informants consist of internal parties (the owner and digital marketing team) and external parties (consumers such as homemakers, resellers, and content creators). The analysis is conducted descriptively based on the SOSTAC framework. The results show that brand awareness is strong offline through word of mouth and direct experience, but still weak in the digital sphere, particularly on TikTok. The digital strategy includes storytelling, segmentation, and omnichannel marketing; however, it is not yet consistent in terms of brand persona and engagement. There is a gap between the effectiveness of offline and digital branding.